Pembentukan Usaha Mikro Kecimpring sebagai Makanan Ciri Khas Kampung Wisata - Muhammad Ari Asy'ari; Ade Irvi Nurul Husna (LPPM Universitas Bina Sarana Informatika, 2023)
With its charming geographical location, Cihanjawar Village can attract tourists from various cities. Therefore, Cihanjawar Village is known as a tourist village. Equipped with villa facilities and infrastructure located in the village of Babakan Villa, RT.05, making this village visited by many tourists every weekend. But unfortunately, in the midst of the large number of tourists who come to the village, as well as rural people living in the mountains in general, the economic life of the babakan villa village community still depends on the agricultural sector, of the 98 heads of families, almost 95% work in the agricultural sector. This makes the economic level of the Babakan Villa community tend to stagnate. Even though agricultural products can be processed into delicious food products and can be a typical product from Babakan Villa Village, RT.05, Cihanjawar Village. One of the abundant agricultural products in Babakan Villa village is Cassava. A small-scale agro-industry whose raw materials are made from cassava is a kecimpring product, this snack is one of the processed products from the Sundanese land. One of the needs that tourists look for when visiting tourist attractions is the typical food of the tourist area. Therefore, through this Community Service Lecture, using the Participatory Action Research (PAR) method, researchers hope that the community will be able to recognize the potential they have, so that they want to make social changes to their potential.